Porcine Reproductive and Respiratory Syndrome Virus strains with Higher Virulence Cause Marked Protein Profile Changes in MARC-145 Cells. Issue 1 (December 2018) - Chen, Zhi; Liu, Shaoning; Zhang, Shujin; Zhang, Yuyu; Yu, Jiang; Sun, Wenbo; Chen, Lei; Du, Yijun; Wang, Jinbao; Li, Yubao; Wu, Jiaqiang
Abstract Porcine reproductive and respiratory syndrome is an infectious disease that causes serious economic losses to the swine industry worldwide. To better understand the pathogenesis of the porcine reproductive and respiratory syndrome virus (PRRSV), three PRRSV strains with different molecular markers and virulence were used to infect MARC-145 cells. A total of 1804 proteins were identified, and 233 altered proteins and 72 signaling pathways involved in the proteomic profiling of virus-infected MARC-145 cells increased with the virulence of the PRRSV strain. The three types of viral strains shared a common pathway—the electron transport reaction in mitochondria—in the infected-MARC-145 cells. Moreover, the antisense pathway was the most variable of all significant signaling pathways for the highly virulent SX-1 strain, indicating that this unique pathway may be connected to the high virulence of the SX-1 strain. Our study is the first attempt to provide a proteome profile of MARC-145 cells infected with PRRSV strains with different virulence, and these findings will facilitate a deep understanding of the interactions between this virus and its host.